THE INFLUENCE OF PRODUCT DESIGN ON PURCHASING DECISIONS OF VIRTUAL ITEMS ON MOBILE LEGENDS BANG-BANG GAME WITH PRICE AS A MODERATION VARIABLE - Effendy, Junko Alessandro; Siswono, Thalia Nikky; Susilo, Fernando Arron; Harliana, Vivia Pauline; Franoto5, Catherine Lorena Valentina (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to find the influence of product design on purchasing decisions with price as a moderating variable. The grand theory in this research is relationship marketing, which is an approach to marketing that emphasizes fostering, developing and maintaining long-term relationships with customers rather than just focusing on short-term buying and selling transactions. Researchers used 3 variables in this research, namely product visuals, price and purchasing decisions. The population in this study was all 110 participants who were members of the esports community in Surabaya. After the researchers distributed the questionnaire, it was found that the response rate for respondents in this study was 74.54% or 82 respondents. The results of the first hypothesis show that product design influences purchasing decisions. The results of the second hypothesis indicate that price negatively moderates the relationship between product design and purchasing decisions Keywords: Relationship marketing, product design, price, purchase decision.